Cognitive instincts versus cognitive gadgets: A fallacy. (28th July 2019) - Roige, Aida; Carruthers, Peter
Abstract: The main thesis of Heyes' book is that all of the domain‐specific learning mechanisms that make the human mind so different from the minds of other animals are culturally created and culturally acquired gadgets . The only innate differences are some motivational tweaks, enhanced capacities for associative learning, and enhanced executive function abilities. But Heyes' argument depends on contrasting cognitive gadgets with cognitive instincts, which are said to be innately specified. This ignores what has for some years been the mainstream nativist/anti‐empiricist view, which commits only to partially specified learning systems that become elaborated and built through domain‐specific learning.